Competitiveness and Flow of Indonesian Paper Trade in The Global Market - Leo Rio Ependi Malau; Nur Arifatul Ulya; Edwin Martin; Raissa Anjani; Bambang Tejo Premono; Tri Yulni (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2022)
Indonesia has the opportunity to increase the share of paper exports in the world due to the declining dominance of NORSCAN (North America and Scandinavia). The momentum is not only an opportunity for Indonesia, but also other paper exporters in Asia and Latin America. This research aims to analyze the competitiveness and determinants of Indonesia’s paper trade flow using secondary data in 2001- 2020 with 11 main export destination countries as objects using Revealed Comparative Advantage (RCA), Export Product Dynamic (EPD) and Gravity models. The RCA analysis showed Indonesia’s paper has competitiveness in 11 export destination countries with diverse growth rates. This is in line with Indonesia’s paper market position as Rising Star in 5 countries which means that Indonesian paper commodities are in a market with high demand growth and market share. Gravity model estimates show that Indonesia and importers real GDP per capita, as well as the level of competitiveness positively affects Indonesia’s paper exports, inversely, export prices and dummy Technical Barrier to Trade (TBT) give negative impact. Based on these results, efforts to increase exports should be done by promoting paper to market with Rising Star and large economies such as China and USA as the priority choices.